Species composition of small mammals in Menchali forest reserve and Bukit Ridan forest reserve - Syed Mohamad, Syarifah Nursyaakirah (2016)
Forest habitat lost and disturbance have affected many fauna species. The study was conducted in two types of forest, Menchali Forest Reserve and Bukit Ridan Forest Reserve, Pahang. The objectives were to compare the species composition of small mammals in hill forest (Bukit Ridan Forest Reserve) and lowland forest (Mechali Forest Reserve) and to determine their diversity, species richness and species evenness. Total number of live traps as 20 and in total 280 trap days was conducted at each forest area (two weeks in Menchali and two weeks in Bukit Ridan). Six lines were established and every single line was positioned with 10 traps. A total of 11 individuals comprising of seven species and two families were recorded. All of the species were from the order Rodentia. This consists of four murids and three sciurids. Lowland forest recorded more individuals (7) compared to hill forest (4). The main factors affecting the species composition and abundance in both study sites was the topography or condition of the forest. Other factor might be because of human disturbance in both areas.